![image](https://tex.z-dn.net/?f=%28x+%2B+5%29%28x+-+1%29%28x+%2B+4%29+x+%3D+176+%5C%5C+%28+%7Bx%7D%5E%7B2%7D++%2B+5x+-+x+-5%29%28+%7Bx%7D%5E%7B2%7D++%2B+4x%29+%3D+176+%5C%5C+%28+%7Bx%7D%5E%7B2%7D++%2B+4x+-+5%29%28+%7Bx%7D%5E%7B2%7D++%2B+4x%29+%3D+176+%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+4x+%3D+t+%5C%5C+%28t+-+5%29t+%3D+176+%5C%5C++%7Bt%7D%5E%7B2%7D++-+5t+-+176+%3D+0+%5C%5C+d+%3D++%7Bb%7D%5E%7B2%7D++-+4ac+%3D+25+-+4+%5Ctimes+%28+-+176%29+%3D+729+%3D++%7B27%7D%5E%7B2%7D++%5C%5C+t1+%3D++%5Cfrac%7B5+%2B+27%7D%7B2%7D++%3D++%5Cfrac%7B32%7D%7B2%7D++%3D+16+%5C%5C+t2+%3D++%5Cfrac%7B5+-+27%7D%7B2%7D+%3D+++%5Cfrac%7B+-+22%7D%7B2%7D++%3D++-+11+%5C%5C+1%29+%7Bx%7D%5E%7B2%7D++%2B+4x+%3D+16+%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+4x+-+16+%3D+0+%5C%5C+d+%3D++%7Bb%7D%5E%7B2%7D++-+4ac+%3D+16+-+4+%5Ctimes+%28+-+16%29+%3D+16+%2B+64+%3D+80+%5C%5C+x1+%3D++%5Cfrac%7B+-+4+%2B++%5Csqrt%7B80%7D+%7D%7B2%7D++%3D++%5Cfrac%7B+-+4+%2B+4+%5Csqrt%7B5%7D+%7D%7B2%7D++%3D++-+2+%2B+2+%5Csqrt%7B5%7D++%5C%5C+x2+%3D++-+2+-++%5Csqrt%7B5%7D++%5C%5C+2%29+%7Bx%7D%5E%7B2%7D++%2B+4x+%3D++-+11+%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+4x+%2B+11+%3D+0+%5C%5C+d+%3D+%7Bb%7D%5E%7B2%7D++-+4ac+%3D+16+-+4+%5Ctimes+11+%3C+0.++%5C%3A++%5C%3A++%5C%3A+%3D++%3E+net+%5C%3A+kornei)
net \: kornei" alt="(x + 5)(x - 1)(x + 4) x = 176 \\ ( {x}^{2} + 5x - x -5)( {x}^{2} + 4x) = 176 \\ ( {x}^{2} + 4x - 5)( {x}^{2} + 4x) = 176 \\ {x}^{2} + 4x = t \\ (t - 5)t = 176 \\ {t}^{2} - 5t - 176 = 0 \\ d = {b}^{2} - 4ac = 25 - 4 \times ( - 176) = 729 = {27}^{2} \\ t1 = \frac{5 + 27}{2} = \frac{32}{2} = 16 \\ t2 = \frac{5 - 27}{2} = \frac{ - 22}{2} = - 11 \\ 1) {x}^{2} + 4x = 16 \\ {x}^{2} + 4x - 16 = 0 \\ d = {b}^{2} - 4ac = 16 - 4 \times ( - 16) = 16 + 64 = 80 \\ x1 = \frac{ - 4 + \sqrt{80} }{2} = \frac{ - 4 + 4 \sqrt{5} }{2} = - 2 + 2 \sqrt{5} \\ x2 = - 2 - \sqrt{5} \\ 2) {x}^{2} + 4x = - 11 \\ {x}^{2} + 4x + 11 = 0 \\ d = {b}^{2} - 4ac = 16 - 4 \times 11 < 0. \: \: \: = > net \: kornei" align="absmiddle" class="latex-formula">
Ответ: -2 +- sqrt(5).